2000
DOI: 10.1093/jjco/hyd028
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of hCG/beta-hCG by Squamous Cell Carcinoma of the Lung in a 31-year-old Female Smoker

Abstract: Abbreviations: hCG, human chorionic gonadotropin; β-hCG, β-subunit of human chorionic gonadotropin; SCC, squamous cell carcinoma; HB, hepatitis type B; NSCLC, non-small cell lung cancer We describe a rare case of pulmonary squamous cell carcinoma secreting human chorionic gonadotropin (hCG) and its β-subunit (β-hCG) in a young female smoker. A 31-year-old mother of one child had been suffering from dysfunctional uterine bleeding for about 1 year. Pelvic examinations and abdominal ultrasonography yielded no abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
0
13
1
Order By: Relevance
“…The hormone is detected in the serum or in the lung tissue itself (11)(12)(13)(14). Dirnhofer et al reported that in various types of lung cancers, ␣-hCG immunoreactivity was detected in 21 of 90 cases, and ␤-hCG in 6 of 90 (13).…”
Section: Hcg-producing Tumors In Reproductive-age Womenmentioning
confidence: 99%
“…The hormone is detected in the serum or in the lung tissue itself (11)(12)(13)(14). Dirnhofer et al reported that in various types of lung cancers, ␣-hCG immunoreactivity was detected in 21 of 90 cases, and ␤-hCG in 6 of 90 (13).…”
Section: Hcg-producing Tumors In Reproductive-age Womenmentioning
confidence: 99%
“…However, after modification of chemotherapy, a partial tumor response with a markedly decrease in β-HCG level was obtained. In another report, Yoshida et al described a case of pulmonary squamous cell carcinoma secreting β-HCG in a young female patient, in whom, after two months of surgery, the β-HCG dropped to normal levels (8).…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of beta-HCG in lung cancer is rare. It has a reported incidence of 14% in small cell lung cancer and 28% in non-small cell lung cancer [12][13][14][15][16][17][18][19] . The reported elevation of beta HCG in lung cancer is about 20-3000 mIU/ml only.…”
Section: Discussionmentioning
confidence: 99%